PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, SERTA PENGARUH PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR INTERNAL PEMERINTAH (Studi Empiris Pada Inspektorat Provinsi Riau) - Nuranisa Nuranisa; Yusralaini Yusralaini; Hanif Afriani Rheny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine and examine the factors that affect the performance of the Government's Internal Auditor. Factors tested in this study are Locus Of Control, Leadership Style, Organizational Culture and Understanding of Good Governance. The data source used in this research is primary data and data collection is done directly using a questionnaire which is measured using a Likert scale. The population in this study were all internal auditors at the Inspectorate of Riau Province, amounting to 47 people. The total sample of this study was 47 respondents which consisted of middle auditors, young auditors, first auditors, advanced executing auditors and executing auditors using a census sampling technique. Data analysis was carried out using multiple linear regression processed with the help of the SPSS version 23 program. The results of this study indicate that Locus of Control, Leadership Style, Organizational Culture, and the Influence of Understanding Good Governance have a significant effect on the Performance of Government Internal Auditors.Keywords: Locus Of Control, Leadership Style, Organizational Culture, Understanding of Good Governance and Performance of Government Internal Auditors